Small-Scale Innovation with Big Impact: Empowering Kader PKK in Lumban Suhi-suhi Village through Ideation Bootcamp: Inovasi Skala Kecil Berdampak Besar: Pemberdayaan Kader PKK Desa Lumban Suhi-suhi melalui Ideation Bootcamp - Eli Jamilah Mihardja; Stella Florensia Hutajulu; Prima Mulyasari Agustini; Holilla Hatta; Raden Aryo Febrian; Dominica Arni Widyastuti (CONSEN: Indonesian Journal of Community Services and Engagement, 2026)
This article aims to describe the implementation of a design thinking-based Ideation Bootcamp to enhance the innovation capacity of MSMEs in Lumban Suhi-suhi Village. The participatory method involved group discussions, simulations, simple prototyping, and action plan formulation. The program successfully engaged 25 MSME owners and generated 5 types of process innovations, such as service standardization and updated consumer communication media. Key indicators showed that 100% of participants actively engaged and independently formulated realistic, low-capital action plans. These findings demonstrate that design thinking serves as an inclusive, cost-effective, and contextual innovation approach for rural communities. This bootcamp has the potential to become an effective, sustainable MSME empowerment model through synergy between higher education and local communities.